Bridging the Gap: Aligning Animal Welfare Ethics with One Health Responsibilities Among Exotic Pet Owners in Indonesia - Averroes Oktaliza; Cinta Ningtiyas; Fitriah Basalamah; Retno Widowati (Journal of Tropical Biodiversity, 2026)
The One Health framework emphasizes interdependence among human, animal, and environmental health, yet exotic pet ownership can create practical tensions between animal welfare ethics and public health responsibility. This mixed methods study examines those tensions among exotic pet owners in Indonesia. A convergent parallel design combined qualitative interviews with 30 owners and a cross-sectional survey. Of 60 survey submissions, eight were excluded because respondents reported cat-only ownership or no current exotic pet, producing a final analytic sample of 52. The Five Domains Model was used as an interview sensitizing guide rather than as a direct welfare scoring framework. Qualitative data were analyzed thematically, while survey data were analyzed using Fisher's exact tests as the primary inferential method, with Yates-corrected chi-square tests disclosed for comparability, Cramer's V for effect size, and Holm and Benjamini-Hochberg corrections for multiple testing. Survey results showed high declarative zoonosis knowledge (47/52, 90.4%), strong vaccination support (41/52, 78.8%), low regular veterinary utilization (16/52, 30.8%), and high zoonosis concern in half of respondents (26/52, 50.0%). Unadjusted Fisher tests suggested associations for veterinary use with vaccination support (p = 0.012) and vaccination support with zoonosis concern (p = 0.038), but no association remained statistically significant after Holm correction. Qualitative findings identified domestic-pet analogy, cleanliness-as-safety beliefs, fragmented zoonosis understanding, inconsistent vaccination practices, community-based knowledge networks, injury normalization, and welfare-focused ethics with limited public-health framing. The integrated findings suggest a value tension within this sample rather than a definitive population-level conflict. One Health interventions should connect public health responsibility to owners' existing welfare commitments while using veterinarians and community networks as complementary communication channels.